Humor as a Didactic Strategy in the Learning of French and English at Los Andes University (2020)
Humor could be a useful strategy in language classes when it comes to pedagogical methods. Humor, laughter, and games create a positive environment in which students feel motivated. Consequently, it increases students' participation and performance during class. Its use significantly reduces the level of students' stress and anxiety. Such